2020
DOI: 10.1002/acn3.51170
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for DYT‐28 dystonia: short term follow‐up of three adult cases

Abstract: Mutations in the lysine methyltransferase 2B (KMT2B) gene have recently been reported to be associated with childhood-onset generalized dystonia. There have been no studies investigating ablative treatments for the management of this disorder. Three patients underwent either a staged unilateral pallidotomy and contralateral pallidothalamic tractotomy (19-year-old man, 2-year follow-up), a unilateral pallidothalamic tractotomy (34-year-old man, 6-month follow-up) or a simultaneous unilateral pallidothalamic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…considered transiently decreased consciousness after pallidothalamic tractotomy (author called campotomy) resulting from lesion encroachment on the ascending reticular activating system. Other previous and current studies of pallidothalamic tractotomy for dystonia, Huntington's disease, and epilepsy did not report transient somnolence 11,32–35 . Here, only two out of 35 patients had transient somnolence (5.7%).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…considered transiently decreased consciousness after pallidothalamic tractotomy (author called campotomy) resulting from lesion encroachment on the ascending reticular activating system. Other previous and current studies of pallidothalamic tractotomy for dystonia, Huntington's disease, and epilepsy did not report transient somnolence 11,32–35 . Here, only two out of 35 patients had transient somnolence (5.7%).…”
Section: Discussioncontrasting
confidence: 41%
“…Other previous and current studies of pallidothalamic tractotomy for dystonia, Huntington's disease, and epilepsy did not report transient somnolence. 11,[32][33][34][35] Here, only two out of 35 patients had transient somnolence (5.7%).…”
Section: Discussionmentioning
confidence: 94%
“…MRgFUS may be the preferred technique for surgical ablation as more transient and less severe adverse effects have been reported compared with radiofrequency ablation[ 86 , 101 , 102 ]. For radiofrequency ablation, electrode placement requires craniotomy or a small burr hole[ 103 , 104 ]. However, recent trials have demonstrated safe bilateral lesioning with this technique[ 104 ].…”
Section: Neurosurgical Managementmentioning
confidence: 99%
“…For radiofrequency ablation, electrode placement requires craniotomy or a small burr hole[ 103 , 104 ]. However, recent trials have demonstrated safe bilateral lesioning with this technique[ 104 ]. Additionally, the capacity for region mapping prior to the procedure gives radiofrequency ablation an upper hand over stereotactic radiosurgery in preoperative surgical preparation.…”
Section: Neurosurgical Managementmentioning
confidence: 99%